An omicron-based vaccine booster elicits potent neutralizing antibodies against emerging SARS-CoV-2 variants in adults - Tao Li; Deyan Luo; Nianzhi Ning; Xin Wang; Liangyan Zhang; Xiaolan Yang; Deyu Li; Yakun Sun; Wenjing Yu; Wenjin Wei; Hui Wang (Emerging Microbes and Infections, 2023)
SARS-CoV-2 Omicron subvariants have become the predominantly strain in most countries. However, the neutralizing activity of the human serum after Omicron-based vaccine booster against different SARS-CoV-2 variants is poorly understood. Here, we developed an update Omicron vaccine (SCoK-Omicron), based on the RBD-Fc fusion protein vaccine (SCoK) and RBD domain of Omicron BA.1. To assess cross-variant neutralizing activity in adults, 25 volunteers that have received three doses of SCoK and 25 volunteers with two doses of CoronaVac (inactive vaccine) were further boosted with a dose updated vaccine (SCoK-Omicron). The results of pseudovirus neutralization assays demonstrated that the booster potently induced the high-level of neutralizing antibody against SARS-CoV-2 Wild type, Delta and Omicron subvariants in adults. Further assays of single point mutations showed that K444T, L452R, N460K, or F486V was key mutations to cause immune evasion. Together, these data suggest that SCOK-Omicron can be used as a booster vaccine candidate in adults receiving subunit protein or inactivated vaccine in response to the epidemic of COVID-19 Omicron subvariants, and the mutation K444T, L452R, N460K, or F486V needs to be considered in future vaccine design.